2017
DOI: 10.1117/1.jbo.22.8.086008
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification of cell morphology by coherence-controlled holographic microscopy

Abstract: Abstract. In the last few years, classification of cells by machine learning has become frequently used in biology. However, most of the approaches are based on morphometric (MO) features, which are not quantitative in terms of cell mass. This may result in poor classification accuracy. Here, we study the potential contribution of coherence-controlled holographic microscopy enabling quantitative phase imaging for the classification of cell morphologies. We compare our approach with the commonly used method bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Whole-slide digital pathology (50) and a high-throughput well-plate culture imaging techniques (51,52) require robust, automated methods to identify cells of clinical interest. The classification accuracy from this study of 90-100% is high, similar to other reported values using machine-learning algorithms trained on optical phase map data (8,49,53). A leaveone-out classification analysis (Supporting Information Table S2) suggested predictive power derived from most of the 17 parameters, which could be reduced to five to six principal components, in accordance with other studies (2,8,49).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Whole-slide digital pathology (50) and a high-throughput well-plate culture imaging techniques (51,52) require robust, automated methods to identify cells of clinical interest. The classification accuracy from this study of 90-100% is high, similar to other reported values using machine-learning algorithms trained on optical phase map data (8,49,53). A leaveone-out classification analysis (Supporting Information Table S2) suggested predictive power derived from most of the 17 parameters, which could be reduced to five to six principal components, in accordance with other studies (2,8,49).…”
Section: Discussionsupporting
confidence: 89%
“…A leaveone-out classification analysis (Supporting Information Table S2) suggested predictive power derived from most of the 17 parameters, which could be reduced to five to six principal components, in accordance with other studies (2,8,49). Taken together, these results indicate that phase parameters from the pixel histogram and gray-level co-occurrence matrix, as well as cell outline-based morphology features (8,32,53), help to classify adherent cell lines. Combining "two-dimensional" and "three-dimensional" phase parameters into signatures input to machine learning makes the algorithm more flexible, as geometric/two-dimensional parameters are likely more important for classifying cell lines of dissimilar shape, and higher-order parameters more important for classifying cell lines of similar shape.…”
Section: Discussionsupporting
confidence: 86%
“…and ). The eleven quantitative parameters from this study overlap in part with morphological and phase parameters found to be useful in other DHM studies of cancer cells . Several other groups using holographic microscopy techniques have tracked migrating cancer cells , and identified phase textures of adherent cancer cells .…”
Section: Discussionmentioning
confidence: 66%
“…Numerous learning approaches are available and have been used on DHM data sets, including deep learning neural networks to distinguish SW480 colon cancer cells in suspension from white blood cells , anthrax from related microorganisms , and to detect and compensate for DHM background and phase aberrations . Machine learning paired with DHM has also recently been used to detect red blood cell infection by P. falciparum , discriminate between isogenic cell lines of differing metastatic stage , distinguish cancer grades from prostate biopsy microarrays , and distinguish healthy and nutrient‐deprived cancer cells , and live and dead yeast cells . Recent commentaries and reviews highlight recent studies combining these two techniques to advance cancer research .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation